What if we just give everything away? - Luke D Lavis (eLife Sciences Publications Ltd, 2021)
A group leader decided that his lab would share the fluorescent dyes they create, for free and without authorship requirements. Nearly 12,000 aliquots later, he reveals what has happened since.